Mortality risk predicts global, local, and individual patterns of human reproduction - Elena Brandt; Jon K. Maner (BMC, 2024)
Abstract Background Human reproductive dynamics in the post-industrial world are typically explained by economic, technological, and social factors including the prevalence of contraception and increasing numbers of women in higher education and the workforce. These factors have been targeted by multiple world governments as part of family policies, yet those policies have had limited success. The current work adopts a life history perspective from evolutionary biology: like most species, human populations may respond to safer environments marked by lower morbidity and mortality by slowing their reproduction and reducing their number of offspring. We test this association on three levels of analysis using global, local, and individual data from publicly available databases. Results Data from over 200 world nations, 3,000 U.S. counties and 2,800 individuals confirm an association between human reproductive outcomes and local mortality risk. Lower local mortality risk predicts "slower" reproduction in humans (lower adolescent fertility, lower total fertility rates, later age of childbearing) on all levels of analyses, even while controlling for socioeconomic variables (female employment, education, contraception). Conclusions The association between extrinsic mortality risk and reproductive outcomes, suggested by life history theory and previously supported by both animal and human data, is now supported by novel evidence in humans. Social and health policies governing human reproduction, whether they seek to boost or constrain fertility, may benefit from incorporating a focus on mortality risk.